Critical Periods during Childhood and Adolescence: A Study of Adult Height among Immigrant Siblings - Gerard J. van den Berg; Petter Lundborg; Paul Nystedt; Dan-Olof Rooth (Lund University, School of Economics and Management, Department of Economics, 2012)
We identify the ages that constitute critical periods in children's development towards their adult health status. For this we use data on families migrating into Sweden from countries that are poorer, with less healthy conditions. Long-run health is proxied by adult height. The relation between siblings' ages at migration and their heights after age 18 allows us to estimate the causal effect of conditions at certain ages on adult height. We effectively exploit that for siblings the migration occurs simultaneously in calendar time but at different developmental stages (ages). We find some evidence that the period just before the puberty growth spurt constitutes a critical period.
Keywords: F22; I10; I12; I18; I20; I30; J10; N30; 330; early-life conditions; migration; parental education; adult health; height retardation; age; fetal programming; developmental origins